"Smart" city" concept for settlements in the Arctic zone of the Russian Federation. Issue 1 (January 2021) - Didenko, N I; Skripnuk, D F; Kulik, S V; Kosinski, Eryk
Abstract: The paper deals with issues related to the use of the concept of a "smart" city. It is concluded that the "smart" city concept is reviewed in the scientific literature and has practical achievements for large cities. The analysis of features of the Arctic zone of the Russian Federation in the context of innovative development is carried out. The analysis of the process of population distribution in the Arctic zone of the Russian Federation and its result - a network of settlements - is presented. The conclusion is made that the Arctic zone should be the place where, first of all, it is necessary to test the "smart" city concept, and the existing network of settlements and interrelation of various types of settlements in the Arctic zone should be used as the objects of using the technologies of the "smart" city concept and their applications. The technologies of the "smart" city concept, which can be used for different types of settlements in the Arctic zone, are determined. The methodological approach taken as the basis for this paper includes: a) an analytical review of literature, focused on the geographical, technological, and institutional characteristics and abilities to implement the concept of sustainable development of the AZRF on the basis of using information and communication technologies (ICT), robotics, and intelligent solutions in the projects of the "smart" city; b) conceptual construction of the real-world virtual cyberspace of the AZRF, or a complex of "socio-cyber-physical systems and intellectual space", which could serve not only for the purposes of monitoring of the mentioned area but in the future could also become a flexible and multi-faceted tool for managing sustainable development of the AZRF. Keywords: Arctic zone of the Russian Federation, development drivers, real-virtual cyberspace, sustainable development, unmanned aerial vehicles.